PENGARUH SOCIAL MEDIA MARKETING DAN NILAI YANG DIRASAKAN (PERCEIVED VALUE) TERHADAP MINAT MENGGUNAKAN KEMBALI PRODUK TELEMEDICINE - Lesmana, Raisya Aurellia Putri; Muhardi, Muhardi; Hendarta, Albert (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2026)
Healthcare access in Indonesia is challenged by an imbalanced doctor-to-patient ratio and an inefficient system, limiting service availability. Telemedicine offers a solution by improving efficiency, saving time for remote patients, and providing health information. Halodoc, one of Indonesia’s most popular telemedicine applications, actively uses social media to promote its services. Social media marketing (SMM) plays an important role in stimulating the intention to reuse Halodoc. Another key factor is perceived value (PV), which reflects users’ evaluation of the benefits and worth of Halodoc’s services. This study aims to examine the impact of Halodoc’s SMM and PV on the intention to reuse its services, both individually and jointly. A descriptive and verificative quantitative approach was employed, with purposive sampling of 97 respondents who had used Halodoc, lived in Bandung, amd have viewed or followed Halodoc’s social media. Data were analyzed using SPSS. The descriptive analysis showed that SMM, PV, and reuse intention were all rated very positively by respondents. The results indicate that SMM has a significant positive effect on reuse intention. Similarly, PV has a significant positive effect on reuse intention. Furthermore, when SMM and PV are analyzed together, they exert a significant combined influence on the intention to reuse Halodoc. These findings highlight the importance of SMM and PV in strengthening user loyalty toward telemedicine services. Keywords: telemedicine, social media marketing, perceived value, reuse intention.